AL-TAZKIYAH AND AL-TA'LIM TERMS IN THE QUR'AN AND THEIR RELATIONSHIP TO THE SEEKING OF KNOWLEDGE: TAQDIM AND TAKHIR STUDIES - Rifaannudin, Mahmud; Asshiddiqy, M. Zaki; Muhammad, Hafid Nur; Agustin, Oky Ayu (Prodi Pendidikan Agama Islam STAI Darul Falah, 2025)
In line with the objectives of education in Indonesia, which seek Knowledge, among others, to form noble morals, there are currently immoral acts committed by students both during education and after graduation. This happens since the education process does not emphasize the aspects of tazkiyah and ta'lim, namely the purification of goodness when seeking Knowledge. Thus, this study aims to determine the relationship between Tazkiyah and Ta'lim for the effectiveness of seeking Knowledge. The researcher employed a descriptive method in explaining the interpretation of the mufassir, then analyzed it to explain the context of the verse. It also used a study of taqdim and takhir to explain the change in the context of the verse on the words al-Tazkiyah and at-Ta'lim. The researcher concluded that tazkiyah is prioritized over Salim because it aligns with the purpose of the Prophet's sending to cleanse or remove humanity from error. The prioritization of tazkiyah over ta'lim shows that before an individual receives Knowledge, the individual should purify by maintaining good intentions and actions before receiving Knowledge since Tazkiyah Nafs can give peace of mind so that it will make it easier to receive Knowledge. Therefore, it is appropriate for students of knowledge to purify their intentions and actions before acquiring knowledge.